LEVELING UP KNOWLEDGE MANAGEMENT: HARNESSING GAMIFICATION FOR EFFECTIVE KNOWLEDGE ACQUISITION, DISTRIBUTION, DISSEMINATION, AND SHARING - Aleksandra Witoszek-Kubicka (Management and Administration Journal, 2024)
The paper addresses the issue of motivating employees to engage in behaviors related to knowledge transfer. This challenge is prevalent in numerous contemporary organizations that seek methods and tools to enhance the effectiveness of acquiring, distributing, disseminating, and sharing knowledge. Within the scope of the article, preliminary research was conducted, including a systematic literature review and a case study based on in-depth interviews and documentation analysis. The aim was to address the following questions: P1: What is the impact of a gamification project on knowledge transfer? P2: Does any objective of internal gamification also aim to support knowledge transfer? The results indicate that knowledge transfer is a pivotal element across all objectives of internal gamification, and the gamification elements positively influence the shaping of desired behaviors within its sub-processes. While these findings stem from preliminary research, they unequivocally underscore the significance of the issue and the necessity for further investigations into the implementation of gamification within organizations, particularly in the context of knowledge transfer. Publication financed by the University of Economics in Krakow under the Support program conference activity – WAK – 2023.